2018
DOI: 10.1115/1.4039569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ride Comfort and Driving Safety for Moving Vehicles on Slender Coastal Bridges

Abstract: Evaluating driving safety of moving vehicles on slender coastal bridges as well as bridge safety is important to provide supporting data to make decisions on continuing or closing the operations of bridges under extreme weather conditions. However, such evaluations could be complicated due to the complex dynamic interactions of vehicle-bridge-wind-wave (VBWW) system. The present study proposes a comprehensive evaluation methodology on vehicle ride comfort and driving safety on the slender coastal bridges subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Te ISO 2631 standard specifes that 12 vibration components sufciently represent the vibration exposure for a seated driver, as illustrated in Figure 4. Previous studies have indicated that the impact of vibration in the vehicle's longitudinal, lateral, and yawn directions on human comfort can generally be neglected [20][21][22]. Terefore, when transferred to the driver, only fve directions of vibrations are typically considered: vertical vibration of the vehicle foor (z f ), vertical vibration of the backrest (z b ), vertical vibration (z s ), pitch vibration (r y ), and roll vibration (r x ) for the seat.…”
Section: New Methods For Evaluating Driving Comfortmentioning
confidence: 99%
“…Te ISO 2631 standard specifes that 12 vibration components sufciently represent the vibration exposure for a seated driver, as illustrated in Figure 4. Previous studies have indicated that the impact of vibration in the vehicle's longitudinal, lateral, and yawn directions on human comfort can generally be neglected [20][21][22]. Terefore, when transferred to the driver, only fve directions of vibrations are typically considered: vertical vibration of the vehicle foor (z f ), vertical vibration of the backrest (z b ), vertical vibration (z s ), pitch vibration (r y ), and roll vibration (r x ) for the seat.…”
Section: New Methods For Evaluating Driving Comfortmentioning
confidence: 99%
“…Most existing evaluation methods for automated vehicles use qualitative evaluation methods, while few quantitative evaluation methods are used. Additionally, most of the existing evaluation methods focus on the performance evaluation of a certain vehicle system [23,24] or on a unilateral performance evaluation of the vehicle (such as an intelligence evaluation [25], comfort evaluation [26], or safety evaluation [27]), and few experts pay attention to the vehicle's comprehensive performance in the existing evaluations of automatic driving systems. Therefore, an evaluation method combining subjective and objective factors is designed and proposed to evaluate the comprehensive performance of automated vehicles.…”
Section: Contribution and Section Arrangementmentioning
confidence: 99%
“…By pertaining all the relevant information, the vehicles can be simplified as several rigid bodies, suspension systems, and tires connected by a series of springs and dampers [22,23]. The vehicle bodies and the tires are simulated as rigid bodies, whereas the elasticity and dissipation capacities of both the suspension system and the tires are idealized as springs and dampers, respectively.…”
Section: Modelling Of Road Vehiclesmentioning
confidence: 99%